Microelectronic component production and packaging process
By adding carbon nanotubes and hyperbranched polymer dispersion stabilizers to the LED packaging materials, the thermal conductivity of fluorescent glue is improved, and the problem of poor thermal conductivity of existing LED packaging materials is solved and the service life of LEDs is extended.
Patent Information
- Application Number
- CN202411640713.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing LED packaging materials such as silicone and epoxy resins have poor thermal conductivity, resulting in the degradation of LED performance after long-term work.
A microelectronic component production and packaging process is adopted to improve the thermal conductivity of the fluorescent glue by adding carbon nanotubes and hyperbranched polymer dispersion stabilizers to the fluorescent glue.
Through graphitization and ultrasonic dispersion technology, an ordered graphite crystal is formed, which improves the thermal conductivity of fluorescent glue and extends the service life of LEDs.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging microelectronic components, and in particular relates to a microelectronic component production packaging process. Background Art
[0002] The full name of CSP is Chip Scale Package, which is chip-scale packaging. According to the definition of CSP in IPC standard J-STD-012, it refers to a fully functional packaged device with a package size ratio of no more than 1.2 times the chip size. The small size, high current and high reliability of CSP LED make CSP LED regarded as the mainstream product of the future by the industry, especially in the fields of mobile phone flash, backlight, and car lights. At present, the thermal resistance of the light source packaged with multiple chips is smaller than that of the light source packaged with a single chip, and the temperature has a certain influence on the thermal stress and reliability of the PCB assembled with multiple devices. The packaging of CSP LED uses fluorescent glue as the packaging material, which plays the role of light conversion output, chip protection, accelerated heat dissipation, reduced the refractive index difference between the chip and the air, and enhanced light output. At present, the commonly used packaging materials are mainly silicone and epoxy resin, but silicone and epoxy resin have poor thermal conductivity, which causes LED performance degradation after long-term operation. Summary of the invention
[0003] The object of the present invention is to provide a microelectronic component production packaging process for improving the thermal conductivity of fluorescent glue used for LED packaging.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A microelectronic component production packaging process comprises the following steps:
[0006] S1, immerse the substrate in anhydrous ethanol for ultrasonic cleaning, and dry it in a hot nitrogen machine to complete the cleaning of the substrate;
[0007] S2, taking a number of LED chips and arranging them on the cleaned substrate according to production requirements;
[0008] S3, preparing fluorescent glue, curing it into a film, cutting it, attaching it to the substrate after the arrangement, pressing the film, baking it, and obtaining the substrate after the film is attached;
[0009] S4, performing line cutting and cleaning, debonding, optical splitting, taping, testing and packaging on the film-attached substrate to obtain a packaged microelectronic component.
[0010] As a preferred technical solution of the present invention, the preparation method of the fluorescent glue comprises the following steps:
[0011] A1. In a nitrogen atmosphere, 1,5-cyclooctadiene palladium dichloride, sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, methyl acrylate and diethyl ether were mixed, stirred at room temperature, filtered, the liquid phase was evaporated under reduced pressure, washed, recrystallized in dichloromethane under low temperature conditions, filtered, and the solid phase was obtained to obtain material A;
[0012] A2, in an ethylene atmosphere, take dichloromethane and 6-bromo-1-hexyl acrylate, mix, stir, add the material A, stir, add tetrahydrofuran and methanol, stir, filter, take the precipitate, wash, vacuum dry, and obtain material B;
[0013] A3. In a nitrogen atmosphere, the material B, hexadecyl acrylate and toluene were mixed, stirred, pentamethyldiethylenetriamine was added, stirred, and freeze-thawed in a cycle, then the temperature was raised to 75°C, cuprous bromide was added, stirring was continued, tetrahydrofuran and methanol were added, stirred, filtered, the precipitate was washed, and vacuum dried to obtain material C;
[0014] A4, taking amino multi-walled carbon nanotubes and N, N-dimethylacetamide, mixing and ultrasonically dispersing to obtain material D;
[0015] A5. In a nitrogen atmosphere, 4,4'-diaminodiphenyl ether, p-phenylenediamine, and N,N-dimethylacetamide were mixed and stirred, and 3,3',4,4'-biphenyltetracarboxylic dianhydride and pyromellitic dianhydride were added while stirring until the system viscosity was 100-120 Pa·s, and the material D was added, ultrasonically dispersed, vacuum degassed, heated in an oven, and then transferred to a carbonization furnace for graphitization in an argon atmosphere, and cooled to room temperature to obtain material E;
[0016] A6. In an argon atmosphere, mix the material C, material E and chloroform, stir ultrasonically, separate by centrifugation, and take the liquid phase to obtain material F;
[0017] A7. In a vacuum atmosphere, epoxy resin, curing agent and accelerator are mixed, heated and stirred, and the material F, sodium citrate, dimethyl phthalate and phosphor are added, and ultrasonic dispersion is performed to obtain the fluorescent glue.
[0018] As a preferred technical solution of the present invention, in step A1, the dosage ratio of 1,5-cyclooctadienepalladium dichloride, sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, methyl acrylate, and ether is 1.13 mmol: 1.13 mmol: 112 μL: 25 mL.
[0019] As a preferred technical solution of the present invention, in step A2, the dosage ratio of dichloromethane, 6-bromo-1-hexyl acrylate, material A, tetrahydrofuran and methanol is 10 mL: 0.28-0.32 mol: 0.2-0.22 g: 150-200 mL: 50-60 mL.
[0020] As a preferred technical solution of the present invention, in step A3, the dosage ratio of material B, hexadecyl acrylate, toluene, pentamethyldiethylenetriamine, cuprous bromide, tetrahydrofuran and methanol is 100 mg: 12-13 g: 15 mL: 45-50 mg: 19-20 mg: 200-300 mL: 100-150 mL.
[0021] As a preferred technical solution of the present invention, in step A4, the ratio of the amino-modified multi-walled carbon nanotubes to N,N-dimethylacetamide is 10-12 g: 100-120 mL.
[0022] As a preferred technical solution of the present invention, in step A5, the dosage ratio of 4,4'-diaminodiphenyl ether, p-phenylenediamine, N,N-dimethylacetamide, 3,3',4,4'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, and material D is 7-8 mol: 3-3.2 mol: 60-80 mL: 7.8-8.2 mol: 2.2-2.4 mol: 1.6-2 mL.
[0023] As a preferred technical solution of the present invention, in step A6, the dosage ratio of material C, material E and chloroform is 80-90 mg: 635-655 mg: 80-100 mL.
[0024] As a preferred technical solution of the present invention, in step A7, the mass ratio of the epoxy resin, curing agent, accelerator, material F, sodium citrate, dimethyl phthalate, and phosphor is 80-100: 3-5: 0.5-0.7: 7.8-9.4: 1-2: 3-4: 15-25.
[0025] Beneficial effects of the present invention:
[0026] The present invention discloses a microelectronic component production and packaging process in which -NH2 groups on the surface of carbon nanotubes can form hydrogen bonds with imide groups -CO-N-CO- on polyimide molecular chains, thereby allowing the carbon nanotubes to be effectively dispersed between polyimide molecular chains. During graphitization treatment, the carbon-carbon structure of the carbon nanotubes serves as microcrystalline nuclei for graphite growth, thereby inducing disordered carbon atoms to rearrange and form ordered graphite crystals. The regular carbon-carbon structure forms a good heat conduction path inside the graphite film, thereby improving the thermal conductivity of the fluorescent glue. In addition, by preparing a hyperbranched polymer dispersing stabilizer, the ordered graphite crystals are uniformly dispersed in the fluorescent glue system, thereby obtaining a fluorescent glue with stable light transmittance and thermal conductivity. DETAILED DESCRIPTION
[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0028] Example 1
[0029] A microelectronic component production packaging process comprises the following steps:
[0030] S1, immerse the substrate in anhydrous ethanol for ultrasonic cleaning for 4 minutes, and dry it in a hot nitrogen machine for 5 minutes to complete the cleaning of the substrate;
[0031] S2, taking a number of LED chips and arranging them on the cleaned substrate according to production requirements;
[0032] S3, preparing fluorescent glue, curing it into a film, cutting it, attaching it to the substrate after the arrangement, pressing the film, baking it, and obtaining the substrate after the film is attached;
[0033] S4, using a cutting machine to perform line cutting and cleaning on the substrate after film pasting, and then using a UV debonding machine to perform debonding, spectroscopy, taping, testing, and packaging to obtain a packaged microelectronic component.
[0034] The preparation method of the fluorescent glue comprises the following steps:
[0035] A1. In a nitrogen atmosphere, 1,5-cyclooctadiene palladium dichloride, sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, methyl acrylate and diethyl ether were mixed, stirred at room temperature for 30 h, filtered, the liquid phase was evaporated under reduced pressure to remove diethyl ether, washed, recrystallized in dichloromethane at a low temperature of -30°C, filtered, and the solid phase was obtained to obtain material A; the dosage ratio of 1,5-cyclooctadiene palladium dichloride, sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, methyl acrylate and diethyl ether was 1.13 mmol: 1.13 mmol: 112 μL: 25 mL;
[0036] A2. In an ethylene atmosphere, mix dichloromethane and 6-bromo-1-hexyl acrylate, stir for 10 min, add the material A, stir for 20 h, add tetrahydrofuran and methanol, stir for 15 min, filter, wash the precipitate, and vacuum dry at 60 ° C for 24 h to obtain material B; the dosage ratio of dichloromethane, 6-bromo-1-hexyl acrylate, material A, tetrahydrofuran, and methanol is 10 mL: 0.28 mol: 0.2 g: 150 mL: 50 mL;
[0037] A3. In a nitrogen atmosphere, mix the material B, hexadecyl acrylate and toluene, stir for 20 min, add pentamethyldiethylenetriamine, stir for 25 min, perform freeze-thaw treatment for 3 cycles, then heat to 75 ° C, add cuprous bromide, continue stirring for 60 min, add tetrahydrofuran and methanol, stir for 15 min, filter, wash the precipitate, and vacuum dry at 60 ° C for 24 h to obtain material C; the dosage ratio of material B, hexadecyl acrylate, toluene, pentamethyldiethylenetriamine, cuprous bromide, tetrahydrofuran and methanol is 100 mg: 12 g: 15 mL: 45 mg: 19 mg: 200 mL: 100 mL;
[0038] A4, taking aminated multi-walled carbon nanotubes (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) and N, N-dimethylacetamide, mixing, ultrasonically dispersing for 15 minutes, to obtain material D; the amount ratio of the aminated multi-walled carbon nanotubes and N, N-dimethylacetamide is 10g:100mL;
[0039] A5. In a nitrogen atmosphere, 4,4'-diaminodiphenyl ether, p-phenylenediamine, and N,N-dimethylacetamide were mixed and stirred for 30 minutes. While stirring, 3,3',4,4'-biphenyltetracarboxylic anhydride and pyromellitic anhydride were added until the viscosity of the system was 100 Pa·s, and the material D was added. Ultrasonic dispersion was performed for 30 minutes, vacuum degassing was performed, and the temperature was increased in an oven. Then, the mixture was transferred to a carbonization furnace and graphitized in an argon atmosphere for 1 hour. The mixture was cooled to room temperature to obtain material E. The dosage ratio of 4,4'-diaminodiphenyl ether, p-phenylenediamine, N,N-dimethylacetamide, 3,3',4,4'-biphenyltetracarboxylic anhydride, pyromellitic anhydride, and material D was 7 mol:3 mol:60 mL:7.8 mol:2.2 mol l: 1.6mL; the heating treatment refers to first keeping the temperature at 150°C for 30 minutes, then heating to 200°C for 20 minutes, then heating to 350°C for 4 minutes, and then heating to 420°C for 2 minutes; the temperature of the graphitization treatment is 2600°C;
[0040] A6. In an argon atmosphere, mix the material C, material E and chloroform, stir ultrasonically for 30 hours, centrifuge and separate the liquid phase to obtain material F; the dosage ratio of the material C, material E and chloroform is 80 mg: 635 mg: 80 mL;
[0041] A7. In a vacuum atmosphere, epoxy resin, curing agent and accelerator are mixed, stirred at 60°C for 1h, material F, sodium citrate, dimethyl phthalate and phosphor are added, and ultrasonic dispersion is performed for 35min to obtain the fluorescent glue; the mass ratio of the epoxy resin, curing agent, accelerator, material F, sodium citrate, dimethyl phthalate and phosphor is 80:3:0.5:7.8:1:3:15; the epoxy resin is epoxy resin E51, purchased from Jinan Jumeihui Chemical Co., Ltd.; the curing agent is polyamide curing agent 650, purchased from Zhongshan Yuanda New Materials Co., Ltd.; the accelerator is accelerator DMP-30, purchased from Wuhan Baiyite Chemical Co., Ltd.; the phosphor is yellow YAG phosphor, purchased from Huizhou Qirong Luminescent Materials Co., Ltd.
[0042] Example 2
[0043] A microelectronic component production packaging process comprises the following steps:
[0044] S1, immerse the substrate in anhydrous ethanol for ultrasonic cleaning for 5 minutes, and dry it in a hot nitrogen machine for 6 minutes to complete the cleaning of the substrate;
[0045] S2, taking a number of LED chips and arranging them on the cleaned substrate according to production requirements;
[0046] S3, preparing fluorescent glue, curing it into a film, cutting it, attaching it to the substrate after the arrangement, pressing the film, baking it, and obtaining the substrate after the film is attached;
[0047] S4, using a cutting machine to perform line cutting and cleaning on the substrate after film pasting, and then using a UV debonding machine to perform debonding, spectroscopy, taping, testing, and packaging to obtain a packaged microelectronic component.
[0048] The preparation method of the fluorescent glue comprises the following steps:
[0049] A1. In a nitrogen atmosphere, 1,5-cyclooctadiene palladium dichloride, sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, methyl acrylate and ether were mixed, stirred at room temperature for 35 h, filtered, the liquid phase was evaporated under reduced pressure to remove ether, washed, recrystallized in dichloromethane at -30°C, filtered, and the solid phase was obtained to obtain material A; the dosage ratio of 1,5-cyclooctadiene palladium dichloride, sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, methyl acrylate and ether was 1.13 mmol:1.13 mmol:112 μL:25 mL;
[0050] A2. In an ethylene atmosphere, dichloromethane and 6-bromo-1-hexyl acrylate were mixed, stirred for 12 min, the material A was added, stirred for 25 h, tetrahydrofuran and methanol were added, stirred for 18 min, filtered, the precipitate was washed, and vacuum dried at 60 ° C for 24 h to obtain material B; the dosage ratio of dichloromethane, 6-bromo-1-hexyl acrylate, material A, tetrahydrofuran, and methanol was 10 mL: 0.3 mol: 0.21 g: 180 mL: 55 mL;
[0051] A3. In a nitrogen atmosphere, mix the material B, hexadecyl acrylate and toluene, stir for 25 min, add pentamethyldiethylenetriamine, stir for 30 min, perform freeze-thaw treatment for 3 times, then heat to 75 ° C, add cuprous bromide, continue stirring for 70 min, add tetrahydrofuran and methanol, stir for 18 min, filter, wash the precipitate, and vacuum dry at 60 ° C for 24 h to obtain material C; the dosage ratio of material B, hexadecyl acrylate, toluene, pentamethyldiethylenetriamine, cuprous bromide, tetrahydrofuran and methanol is 100 mg: 12.5 g: 15 mL: 48 mg: 19.5 mg: 250 mL: 125 mL;
[0052] A4, take amino multi-walled carbon nanotubes (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) and N, N-dimethylacetamide, mix, and ultrasonically disperse for 20 minutes to obtain material D; the amount ratio of the amino multi-walled carbon nanotubes and N, N-dimethylacetamide is 11g:110mL;
[0053] A5. In a nitrogen atmosphere, 4,4'-diaminodiphenyl ether, p-phenylenediamine, and N,N-dimethylacetamide were mixed and stirred for 35 minutes. While stirring, 3,3',4,4'-biphenyltetracarboxylic anhydride and pyromellitic anhydride were added until the system viscosity reached 110 Pa·s, and the material D was added. Ultrasonic dispersion was performed for 35 minutes, and vacuum degassing was performed. The mixture was heated in an oven, and then transferred to a carbonization furnace for graphitization treatment in an argon atmosphere for 1.1 hours. The mixture was cooled to room temperature to obtain material E. The dosage ratio of 4,4'-diaminodiphenyl ether, p-phenylenediamine, N,N-dimethylacetamide, 3,3',4,4'-biphenyltetracarboxylic anhydride, pyromellitic anhydride, and material D was 7.5 mol:3.1 mol:70 mL:8 mol:2.3 mol l: 1.8mL; the heating treatment refers to first keeping the temperature at 150°C for 35 minutes, then heating to 200°C for 25 minutes, then heating to 350°C for 5 minutes, and then heating to 420°C for 2.5 minutes; the temperature of the graphitization treatment is 2700°C;
[0054] A6. In an argon atmosphere, mix the material C, material E and chloroform, stir ultrasonically for 35 hours, centrifuge and separate the liquid phase to obtain material F; the dosage ratio of the material C, material E and chloroform is 85 mg: 645 mg: 90 mL;
[0055] A7. In a vacuum atmosphere, epoxy resin, curing agent and accelerator are mixed, stirred at 70°C for 1.1h, material F, sodium citrate, dimethyl phthalate and phosphor are added, and ultrasonic dispersion is performed for 40min to obtain the fluorescent glue; the mass ratio of the epoxy resin, curing agent, accelerator, material F, sodium citrate, dimethyl phthalate and phosphor is 90:4:0.6:8.6:1.5:3.5:20; the epoxy resin is epoxy resin E51, purchased from Jinan Jumeihui Chemical Co., Ltd.; the curing agent is polyamide curing agent 650, purchased from Zhongshan Yuanda New Materials Co., Ltd.; the accelerator is accelerator DMP-30, purchased from Wuhan Baiyite Chemical Co., Ltd.; the phosphor is yellow YAG phosphor, purchased from Huizhou Qirong Luminescent Materials Co., Ltd.
[0056] Example 3
[0057] A microelectronic component production packaging process comprises the following steps:
[0058] S1, immerse the substrate in anhydrous ethanol for ultrasonic cleaning for 6 minutes, and dry it in a hot nitrogen machine for 7 minutes to complete the cleaning of the substrate;
[0059] S2, taking a number of LED chips and arranging them on the cleaned substrate according to production requirements;
[0060] S3, preparing fluorescent glue, curing it into a film, cutting it, attaching it to the substrate after the arrangement, pressing the film, baking it, and obtaining the substrate after the film is attached;
[0061] S4, using a cutting machine to perform line cutting and cleaning on the substrate after film pasting, and then using a UV debonding machine to perform debonding, spectroscopy, taping, testing, and packaging to obtain a packaged microelectronic component.
[0062] The preparation method of the fluorescent glue comprises the following steps:
[0063] A1. In a nitrogen atmosphere, 1,5-cyclooctadiene palladium dichloride, sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, methyl acrylate and diethyl ether were mixed, stirred at room temperature for 40 h, filtered, the liquid phase was evaporated under reduced pressure to remove diethyl ether, washed, recrystallized in dichloromethane at a low temperature of -30°C, filtered, and the solid phase was obtained to obtain material A; the dosage ratio of 1,5-cyclooctadiene palladium dichloride, sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, methyl acrylate and diethyl ether was 1.13 mmol:1.13 mmol:112 μL:25 mL;
[0064] A2. In an ethylene atmosphere, take dichloromethane and 6-bromo-1-hexyl acrylate, mix them, stir for 15 minutes, add the material A, stir for 30 hours, add tetrahydrofuran and methanol, stir for 20 minutes, filter, wash the precipitate, and vacuum dry it at 60°C for 24 hours to obtain material B; the dosage ratio of dichloromethane, 6-bromo-1-hexyl acrylate, material A, tetrahydrofuran, and methanol is 10mL: 0.32mol: 0.22g: 200mL: 60mL;
[0065] A3. In a nitrogen atmosphere, mix the material B, hexadecyl acrylate and toluene, stir for 30 min, add pentamethyldiethylenetriamine, stir for 35 min, perform freeze-thaw treatment for 3 times, then heat to 75 ° C, add cuprous bromide, continue stirring for 80 min, add tetrahydrofuran and methanol, stir for 20 min, filter, wash the precipitate, and vacuum dry at 60 ° C for 24 h to obtain material C; the dosage ratio of material B, hexadecyl acrylate, toluene, pentamethyldiethylenetriamine, cuprous bromide, tetrahydrofuran and methanol is 100 mg: 13 g: 15 mL: 50 mg: 20 mg: 300 mL: 150 mL;
[0066] A4, take amino multi-walled carbon nanotubes (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) and N, N-dimethylacetamide, mix, and ultrasonically disperse for 25 minutes to obtain material D; the amount ratio of the amino multi-walled carbon nanotubes and N, N-dimethylacetamide is 12g:120mL;
[0067] A5. In a nitrogen atmosphere, 4,4'-diaminodiphenyl ether, p-phenylenediamine, and N,N-dimethylacetamide were mixed and stirred for 40 min. 3,3',4,4'-biphenyltetracarboxylic anhydride and pyromellitic anhydride were added while stirring until the viscosity of the system was 120 Pa·s, and the material D was added. Ultrasonic dispersion was performed for 40 min, vacuum degassing was performed, and the temperature was increased in an oven. Then, the mixture was transferred to a carbonization furnace and graphitized in an argon atmosphere for 1.2 h. The mixture was cooled to room temperature to obtain material E. The dosage ratio of 4,4'-diaminodiphenyl ether, p-phenylenediamine, N,N-dimethylacetamide, 3,3',4,4'-biphenyltetracarboxylic anhydride, pyromellitic anhydride, and material D was 8 mol:3.2 mol:80 mL:8.2 mol:2.4 mol l: 2mL; the heating treatment refers to first keeping the temperature at 150°C for 40 minutes, then heating to 200°C for 30 minutes, then heating to 350°C for 6 minutes, and then heating to 420°C for 3 minutes; the temperature of the graphitization treatment is 2800°C;
[0068] A6. In an argon atmosphere, mix the material C, material E and chloroform, stir ultrasonically for 40 hours, centrifuge and separate the liquid phase to obtain material F; the dosage ratio of the material C, material E and chloroform is 90 mg: 655 mg: 100 mL;
[0069] A7. In a vacuum atmosphere, epoxy resin, curing agent and accelerator are mixed, stirred at 80°C for 1.2h, material F, sodium citrate, dimethyl phthalate and phosphor are added, and ultrasonic dispersion is performed for 45min to obtain the fluorescent glue; the mass ratio of the epoxy resin, curing agent, accelerator, material F, sodium citrate, dimethyl phthalate and phosphor is 100:5:0.7:9.4:2:4:25; the epoxy resin is epoxy resin E51, purchased from Jinan Jumeihui Chemical Co., Ltd.; the curing agent is polyamide curing agent 650, purchased from Zhongshan Yuanda New Materials Co., Ltd.; the accelerator is accelerator DMP-30, purchased from Wuhan Baiyite Chemical Co., Ltd.; the phosphor is yellow YAG phosphor, purchased from Huizhou Qirong Luminescent Materials Co., Ltd.
[0070] Comparative Example 1
[0071] The difference from Example 2 is that the method for preparing the fluorescent glue comprises the following steps:
[0072] A1. In a nitrogen atmosphere, 1,5-cyclooctadiene palladium dichloride, sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, methyl acrylate and ether were mixed, stirred at room temperature for 35 h, filtered, the liquid phase was evaporated under reduced pressure to remove ether, washed, recrystallized in dichloromethane at -30°C, filtered, and the solid phase was obtained to obtain material A; the dosage ratio of 1,5-cyclooctadiene palladium dichloride, sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, methyl acrylate and ether was 1.13 mmol:1.13 mmol:112 μL:25 mL;
[0073] A2. In an ethylene atmosphere, dichloromethane and 6-bromo-1-hexyl acrylate were mixed, stirred for 12 min, the material A was added, stirred for 25 h, tetrahydrofuran and methanol were added, stirred for 18 min, filtered, the precipitate was washed, and vacuum dried at 60 ° C for 24 h to obtain material B; the dosage ratio of dichloromethane, 6-bromo-1-hexyl acrylate, material A, tetrahydrofuran, and methanol was 10 mL: 0.3 mol: 0.21 g: 180 mL: 55 mL;
[0074] A3. In a nitrogen atmosphere, mix the material B, hexadecyl acrylate and toluene, stir for 25 min, add pentamethyldiethylenetriamine, stir for 30 min, perform freeze-thaw treatment for 3 times, then heat to 75 ° C, add cuprous bromide, continue stirring for 70 min, add tetrahydrofuran and methanol, stir for 18 min, filter, wash the precipitate, and vacuum dry at 60 ° C for 24 h to obtain material C; the dosage ratio of material B, hexadecyl acrylate, toluene, pentamethyldiethylenetriamine, cuprous bromide, tetrahydrofuran and methanol is 100 mg: 12.5 g: 15 mL: 48 mg: 19.5 mg: 250 mL: 125 mL;
[0075] A4. In an argon atmosphere, the material C, flake graphite and chloroform were mixed, ultrasonically stirred for 35 hours, centrifuged and separated, and the liquid phase was taken to obtain material F; the dosage ratio of the material C, flake graphite and chloroform was 85 mg: 645 mg: 90 mL;
[0076] A5. In a vacuum atmosphere, epoxy resin, curing agent and accelerator are mixed, stirred at 70°C for 1.1h, material F, sodium citrate, dimethyl phthalate and phosphor are added, and ultrasonic dispersion is performed for 40min to obtain the fluorescent glue; the mass ratio of the epoxy resin, curing agent, accelerator, material F, sodium citrate, dimethyl phthalate and phosphor is 90:4:0.6:8.6:1.5:3.5:20; the epoxy resin is epoxy resin E51; the curing agent is polyamide curing agent 650; the accelerator is accelerator DMP-30; the phosphor is yellow YAG phosphor.
[0077] Comparative Example 2
[0078] The difference from Example 2 is that the method for preparing the fluorescent glue comprises the following steps:
[0079] A1, taking aminated multi-walled carbon nanotubes and N, N-dimethylacetamide, mixing, and ultrasonically dispersing for 20 minutes to obtain material D; the amount ratio of the aminated multi-walled carbon nanotubes and N, N-dimethylacetamide is 11g:110mL;
[0080] A2. In a nitrogen atmosphere, 4,4'-diaminodiphenyl ether, p-phenylenediamine, and N,N-dimethylacetamide were mixed and stirred for 35 minutes. While stirring, 3,3',4,4'-biphenyltetracarboxylic anhydride and pyromellitic anhydride were added until the system viscosity reached 110 Pa·s, and the material D was added. Ultrasonic dispersion was performed for 35 minutes, vacuum degassing was performed, and the temperature was increased in an oven. Then, the mixture was transferred to a carbonization furnace and graphitized in an argon atmosphere for 1.1 hours. The mixture was cooled to room temperature to obtain material E. The dosage ratio of 4,4'-diaminodiphenyl ether, p-phenylenediamine, N,N-dimethylacetamide, 3,3',4,4'-biphenyltetracarboxylic anhydride, pyromellitic anhydride, and material D was 7.5 mol:3.1 mol:70 mL:8 mol:2.3 mol l: 1.8mL; the heating treatment refers to first keeping the temperature at 150°C for 35 minutes, then heating to 200°C for 25 minutes, then heating to 350°C for 5 minutes, and then heating to 420°C for 2.5 minutes; the temperature of the graphitization treatment is 2700°C;
[0081] A3. In an argon atmosphere, the material E and chloroform were mixed, ultrasonically stirred for 35 hours, centrifuged, and the liquid phase was taken to obtain material F; the dosage ratio of the material E to chloroform was 645 mg: 90 mL;
[0082] A4. In a vacuum atmosphere, epoxy resin, curing agent and accelerator are mixed, stirred at 70°C for 1.1h, material F, sodium citrate, dimethyl phthalate and phosphor are added, and ultrasonic dispersion is performed for 40min to obtain the fluorescent glue; the mass ratio of the epoxy resin, curing agent, accelerator, material F, sodium citrate, dimethyl phthalate and phosphor is 90:4:0.6:8.6:1.5:3.5:20; the epoxy resin is epoxy resin E51; the curing agent is polyamide curing agent 650; the accelerator is accelerator DMP-30; the phosphor is yellow YAG phosphor.
[0083] Performance Testing
[0084] The fluorescent glue prepared in Examples 1-3 and Comparative Examples 1-2 was cast into a mold and heated to 100°C in a vacuum oven for 2 hours, then heated to 180°C and maintained for 30 minutes for curing. The mold was demolded to obtain a fluorescent glue film with a size of 30mm*20mm*2mm. The transmittance of the fluorescent glue film was tested (determined by the spectrophotometer method of GB / T 2410-2008, wavelength 467nm) and the thermal conductivity test (determined by ASTM D5470) were tested. The test results are shown in Table 1 below.
[0085] Table 1
[0086] Light transmittance (%) Cross-sectional thermal conductivity (W / m·K) Example 1 98.73 30.87 Example 2 99.12 30.94 Example 3 98.91 30.82 Comparative Example 1 93.74 23.84 Comparative Example 2 93.67 23.15
[0087] As can be seen from Table 1, the fluorescent glue prepared in Examples 1-3 of the present application has good light transmittance and thermal conductivity. The present application allows the -NH2 groups on the surface of the carbon nanotubes to form hydrogen bonds with the imide groups -CO-N-CO- on the polyimide molecular chains, so that the carbon nanotubes can be effectively dispersed between the polyimide molecular chains. During graphitization, the carbon-carbon structure of the carbon nanotubes serves as the microcrystalline nucleus of graphite growth, thereby inducing disordered carbon atoms to rearrange and form ordered graphite crystals. The regular carbon-carbon structure forms a good thermal conductivity path inside the graphite film, thereby improving the thermal conductivity of the fluorescent glue. In addition, by preparing a hyperbranched polymer dispersing stabilizer, the ordered graphite crystals are evenly dispersed in the fluorescent glue system, thereby obtaining a fluorescent glue with stable light transmittance and thermal conductivity.
[0088] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A microelectronic component production packaging process, characterized in that: The following steps are involved: S1, immerse the substrate in anhydrous ethanol for ultrasonic cleaning, and dry it in a hot nitrogen machine to complete the cleaning of the substrate; S2, taking a number of LED chips and arranging them on the cleaned substrate according to production requirements; S3, preparing fluorescent glue, curing it into a film, cutting it, attaching it to the substrate after the arrangement, pressing the film, baking it, and obtaining the substrate after the film is attached; S4, performing line cutting and cleaning, debonding, optical splitting, taping, testing and packaging on the film-attached substrate to obtain a packaged microelectronic component.
2. A microelectronic component production and packaging process according to claim 1, characterized in that: The preparation method of the fluorescent glue comprises the following steps: A1. In a nitrogen atmosphere, 1,5-cyclooctadiene palladium dichloride, sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, methyl acrylate and diethyl ether were mixed, stirred at room temperature, filtered, the liquid phase was evaporated under reduced pressure, washed, recrystallized in dichloromethane under low temperature conditions, filtered, and the solid phase was obtained to obtain material A; A2, in an ethylene atmosphere, take dichloromethane and 6-bromo-1-hexyl acrylate, mix, stir, add the material A, stir, add tetrahydrofuran and methanol, stir, filter, take the precipitate, wash, vacuum dry, and obtain material B; A3. In a nitrogen atmosphere, the material B, hexadecyl acrylate and toluene were mixed, stirred, pentamethyldiethylenetriamine was added, stirred, and freeze-thawed in a cycle, then the temperature was raised to 75°C, cuprous bromide was added, stirring was continued, tetrahydrofuran and methanol were added, stirred, filtered, the precipitate was washed, and vacuum dried to obtain material C; A4, taking amino multi-walled carbon nanotubes and N, N-dimethylacetamide, mixing and ultrasonically dispersing to obtain material D; A5. In a nitrogen atmosphere, 4,4'-diaminodiphenyl ether, p-phenylenediamine, and N,N-dimethylacetamide were mixed and stirred, and 3,3',4,4'-biphenyltetracarboxylic dianhydride and pyromellitic dianhydride were added while stirring until the system viscosity was 100-120 Pa·s, and the material D was added, ultrasonically dispersed, vacuum degassed, heated in an oven, and then transferred to a carbonization furnace for graphitization in an argon atmosphere, and cooled to room temperature to obtain material E; A6. In an argon atmosphere, mix the material C, material E and chloroform, stir ultrasonically, separate by centrifugation, and take the liquid phase to obtain material F; A7. In a vacuum atmosphere, epoxy resin, curing agent and accelerator are mixed, heated and stirred, and the material F, sodium citrate, dimethyl phthalate and phosphor are added, and ultrasonic dispersion is performed to obtain the fluorescent glue.
3. A microelectronic component production and packaging process according to claim 2, characterized in that: In step A1, the dosage ratio of 1,5-cyclooctadienepalladium dichloride, sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, methyl acrylate, and diethyl ether is 1.13 mmol: 1.13 mmol: 112 μL: 25 mL.
4. A microelectronic component production and packaging process according to claim 2, characterized in that: In step A2, the dosage ratio of dichloromethane, 6-bromo-1-hexyl acrylate, material A, tetrahydrofuran and methanol is 10 mL: 0.28-0.32 mol: 0.2-0.22 g: 150-200 mL: 50-60 mL.
5. A microelectronic component production and packaging process according to claim 2, characterized in that: In step A3, the dosage ratio of material B, hexadecyl acrylate, toluene, pentamethyldiethylenetriamine, cuprous bromide, tetrahydrofuran, and methanol is 100 mg: 12-13 g: 15 mL: 45-50 mg: 19-20 mg: 200-300 mL: 100-150 mL.
6. A microelectronic component production and packaging process according to claim 2, characterized in that: In step A4, the ratio of the amino-modified multi-walled carbon nanotubes to N,N-dimethylacetamide is 10-12 g: 100-120 mL.
7. A microelectronic component production and packaging process according to claim 2, characterized in that: In step A5, the dosage ratio of 4,4'-diaminodiphenyl ether, p-phenylenediamine, N,N-dimethylacetamide, 3,3',4,4'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, and material D is 7-8 mol: 3-3.2 mol: 60-80 mL: 7.8-8.2 mol: 2.2-2.4 mol: 1.6-2 mL.
8. A microelectronic component production and packaging process according to claim 2, characterized in that: In step A6, the dosage ratio of material C, material E and chloroform is 80-90 mg: 635-655 mg: 80-100 mL.
9. A microelectronic component production and packaging process according to claim 2, characterized in that: In step A7, the mass ratio of the epoxy resin, the curing agent, the accelerator, the material F, the sodium citrate, the dimethyl phthalate, and the phosphor is 80-100: 3-5: 0.5-0.7: 7.8-9.4: 1-2: 3-4: 15-25.